Trauma, angústia e desautorização nos dispositivos de saúde materno-infantil em contextos de vulnerabilidade social: contribuições clínico-políticas da psicanálise - Teixeira, Iara Fernandes (2019)
The latest data on the living conditions and development of children in Brazil are quite expressive as for the effects of social and regional inequalities in the quality of public policies. In this context, the present dissertation aims to propose, from the psychoanalytic concepts of trauma, anguish and disempowerment of the subject at its intersections with the conceptual fields of social sciences and of social psychology, the construction of ethical political assumptions to a clinic of the vulnerabilities of the maternal and child health care. In order to achieve our general objective, we set out the following specific objectives: to discuss the bases of the concept of vulnerability in articulation with the concepts of social recognition, dignity and poverty; to rescue the assumptions of the theory of trauma and anguish in Freud and Ferenczi and of the de-authorization of the subject; and, finally, to discuss some ethical-political assumptions for a clinical practice in the field of maternal and child health, from the questioning of the observations in IPREDE. We made use of the field journal as metapsychological tool, which allowed us to define our goals, allies to question, the categories which would nodal sustain atheoretical argument and the articulation with the participant observation conducted in IPREDE. After exploring how our concerns met, we research on the different meanings of the concept of vulnerability seeking to relate this to the concept of human dignity from the context in which the dignity mention the horror of war and so, when you meet with the face of trauma. In dialogue with social/community psychology, we are discussing about the naturalization processes and scapegoating of poverty as important operators in maintaining a place of exclusion of the subject in the social bond. Based on these discussions, we propose to reaffirm the ethical-political commitment of psychoanalysis and to point out some important assumptions for attention to maternal and child health in contexts of helplessness and traumatic vulnerabilities. As a conclusion, we highlight clinical-political operators as important assumptions in the construction of a clinical practice involved in listening to sociopolitical suffering, namely: recognition of the place of knowledge / power of the subject, the relationship of trust established between user and professional, the incentive to the spontaneity and participation of the subject in his care process.